Ecopreneurship – Assessing the field and outlining the research potential. Issue 1 (2nd January 2016) - Galkina, Tamara; Hultman, Martin
Abstract : This article assesses ecopreneurship from the point of view of an admittance-seeking social movement. We use the three criteria for evaluating the present status of the ecopreneurship research domain - differentiation, mobolization, and legitimacy building. Our analysis shows that ecopreneurship is still in the early stages of its development as a field of academic study, thus its further development in terms of theoretical contributions, questions to be asked, and research design must be understood in relation to its current status. We conclude that ecopreneurship research should remain open to the contributions from other fields of study in order to formulate its goals more precisely and to build a more solid foundation as an area of scientific inquiry.